2016
DOI: 10.1007/s00408-016-9904-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sarcomatoid Carcinoma of the Lung: Radiometabolic (18F-FDG PET/CT) Findings and Correlation with Clinico-Pathological and Survival Results

Abstract: No differences in terms of SUVmax were found with regard to tumour dimensions, histology (pure vs mixed, pleomorphic vs others), pathological stage and pattern of recurrence. P-stage, surgical radicality, vascular/lymphatic invasion but not SUVmax affected long-term survival in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
(18 reference statements)
2
10
1
1
Order By: Relevance
“…In our study, the presence of a cavity remained as an important SRS model; however, the semantic feature was removed from the list of CRS model. We cannot explain exquisitely the difference in results between our study and the previous one [ 10 ]. But the multivariate nature of our radiomics or combined model, not univariate nature, might help explain the difference in the results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, the presence of a cavity remained as an important SRS model; however, the semantic feature was removed from the list of CRS model. We cannot explain exquisitely the difference in results between our study and the previous one [ 10 ]. But the multivariate nature of our radiomics or combined model, not univariate nature, might help explain the difference in the results.…”
Section: Discussioncontrasting
confidence: 99%
“…The total lesion glycolysis (TLG) of the primary tumor and KRAS mutation were independent prognostic factors of PCs [ 9 ]. In an additional PET/CT study [ 10 ], tumor SUVmax was not different in terms of tumor dimensions, histology, pathological stage, and pattern of recurrence. Pathologic stage, surgical completeness, and the presence of vascular or lymphatic invasion were related factors for patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients who had metastatic disease had poor PS and the proportion of patients who received first-line or subsequent lines of therapy was low, which reflects the aggressive disease biology. We found that the median SUV max of the tumour on the baseline PET-CT was 20.2, which is similar to that reported in other studies which reported that PSC has intense SUV uptake values [28,29]. This suggests that PSCs are F-fluorodeoxyglucose (FDG)-avid tumours and that performing a PET-CT scan would be an appropriate staging test, especially in patients who are being planned for radical therapy.…”
Section: Discussionsupporting
confidence: 87%
“…41 At imaging studies, PSC may present as either a central or peripheral location. 2,5,24,42 Pleomorphic carcinomas with squamous cell carcinoma component and carcinosarcoma may show a peculiar endobronchial, polypoid appearance ( Figure 2), while peripheral PSC typically manifests as a large mass (over 10 cm) with rounded, well-defined margins (Figures 3 and 4) with necrotic and/or hemorrhagic areas and soft surface with/without cavitation ( Figure 5).…”
Section: Epidemiology Imaging Studies Clinical Featuresmentioning
confidence: 99%